ESTETIKA FASAD PADA BANGUNAN KOLONIAL 1920-1940 - Savitri Savitri (Jurusan Seni Rupa ISBI Bandung, 2013)
Fasad is the face of a building, a front or outer appearance, especially a deceptive one. To judge a façade is a very subjective matter. However to design for public also means having the correct way in doing it. Building faces, display windows, and stage backdrops are also parts of façade to design. By using aesthetic theory we can create façade with proper visual for public, and analyze which façade is aesthetically balance. Colonial building’s façade is a façade with spesific character which posess good visual language. This research will study about the uniqueness of colonial building’s façade by using aesthethic principle theory. The balance in colonial bulding’s façade will become an exemplary on how a good façade is suppose to be, a façade with an aesthetic unity.Keywords: Building’s Fasade, Aesthetic Value, Colonial Buildings